A dataset on the community impacts of deindustrialisation and COVID-19 in Australia - Jacob Irving; Andrew Beer; Markku Sotarauta (Scientific Data)
Abstract The Australian automotive plant closures of 2016 and 2017 led to mass retrenchment and deindustrialisation, and resulted in lasting impacts on workers, families and communities in the locations surrounding former car assembly plants. A large-scale program of research began in 2019 as a multi-university collaboration to examine the impacts of industry restructuring, including a stream of work dedicated to investigating community confidence in the economy and leadership following the closures and during the COVID-19 health crisis. This paper introduces a 2021 Community Survey dataset that encompasses these perspectives from affected communities directly surrounding the plant sites, as well as the those from the broader population of the two state capital cities in which these communities were located. This dataset is designed to aid researchers and policy makers in understanding the role of leaders during periods of crisis and industry restructuring. A total of 1,755 responses were recorded.